Relationship between religion, state, and politics: A study of the dynamics of islamic education in Indonesia - Sya'bani, Mohammad Ahyan Yusuf (Universitas Ahmad Dahlan, 2025)
The purpose of this research is to formulate Islamic education within the Indonesian context as a subsystem of the aspects of religion, state, and politics themselves. Therefore, it is essential to reformulate the position of Islamic education in the context of the nation and state as a representation of the aspects of religion, state, and politics. The background of this research is that Islamic education currently experiences a disorientation of purpose and a marginalized dominance of existence. For example, many Islamic educational institutions do not experience a significant increase in student enrollment, which could be due to a lack of contextual Islamic knowledge or unprofessional institutional management systems. Facing such a situation, it is important to find solutions so that Islamic education becomes more responsive to the fields of religion, state, and politics, so that it can adapt to national and state life. This research uses a qualitative method with a literature review type of research and a grounded theory approach. Data collection techniques use literature and documentation from various sources. Data analysis then uses heuristic analysis, verification, interpretation, and synthesis. The results of this research are that initially, there were three types of relationships between religion, state, and politics: religiously unfriendly secularism, religiously friendly ideology, and theocratic system. In the Indonesian context, which refers to a religiously friendly ideology system, Islamic education within the framework of the relationship between religion, state, and politics in Indonesia means that Islamic education about religion serves as a moral guide, Islamic education about the state serves as a system, constitution, and medium, and Islamic education about politics is about policy and social aspects. The conclusion obtained shows that these three aspects, namely religion, state, and politics, in the dynamics of Islamic education in Indonesia are formulated in social, governance, and environmental terms. This means that Islamic education as the basis of religion in Indonesia has a social role to shape the noble character of its society, Islamic education viewed from the perspective of the state is to implement a holistic system so that it can function optimally in society (governance), and Islamic education as politics is to be able to create and form a peaceful and prosperous environment.